Loyalty Toward Shoope-food Delivery Service: The Role of E-Service Quality and Food Quality - Ghifari Ghaza Nugraha; Juliani Dyah Trisnawati; Widjaja, Fitri Novika (Journal of Entrepreneurship and Business, 2024)
Purpose: This study investigates 14 hypotheses concerning e-service quality, perceived value, food quality, customer satisfaction, and customer loyalty. Method: This research uses a quantitative approach. Data is collected from 137 Surabaya residents who frequently use the Shopee Food app to buy food and drinks. The analysis employs Structural Equation Modelling (SEM) with Smart PLS software. Result: The results showed a positive and significant influence of e-service quality on perceived value, customer loyalty, and food quality. Food quality and perceived value also have a positive and significant effect. However, there was no significant effect between food quality, customer satisfaction, and customer loyalty. The study also found a positive and significant effect between perceived value on customer satisfaction and customer loyalty, as well as customer satisfaction on customer loyalty. Also, there is a positive and significant effect between e-service quality and customer loyalty mediated by perceived value and food quality on customer loyalty mediated by perceived value. Interestingly, there was no significant effect between e-service quality and customer loyalty mediated by customer satisfaction and food quality on customer loyalty mediated by customer satisfaction.